Global Coordination in Plant Physiological and Rooting Strategies in Response to Water Stress. Issue 7 (2nd July 2021) - Liu, Yaling; Konings, Alexandra G.; Kennedy, Daniel; Gentine, Pierre
Abstract: Plants employ a range of strategies to modulate the impact of water stress, including changes to rooting depth and hydraulic conductance (e.g., xylem conductance). However, it is still poorly understood how these strategies vary in relation to climate and land cover types and how they could coordinate globally. Based on daily microwave vegetation optical depth (VOD) from AMSR‐E and AMSR2 over 2002–2011, we estimate two proxies for stress regulation: (a) an effective plant rooting depth ( Z r ∗ ) and (b) the effective plant hydraulic conductance ( K plant ∗ ) to delineate two strategies: deep rooting and strong physiological regulation. We find that plants with deeper Z r ∗ (e.g., evergreen/deciduous broadleaf forest) are mostly distributed in warm or wet regions, and maintain a relatively steady nighttime VOD because of access to deeper water. Taller plants exhibit greater drop in daytime VOD due to their greater physiological vulnerability. While physiological regulation appears to be the dominant water stress regulation strategy at Northern high latitudes where open shrubland and (woody) savannas are distributed, this physiological regulation is coupled with deep rooting in forest and (woody) savanna areas in the tropics, Eastern US, and Southeastern China. Meanwhile, grasslands in the Western US, Central Asia, Northeastern China, and Mongolia Plateau may be the regions most susceptible to water stress impact because neither water stress mitigation strategy is present. This new framework paves the road for a better understanding of plant water stress strategies at the global scale, and for enhancing large‐scale drought prediction and drought impact assessment in Earth system models by improving plant water stress response. Key Points: Plants with deeper roots maintain relatively steady nighttime vegetation optical depth (VOD) and taller plants drop daytime VOD more Physiological regulation is the dominant strategy in Northern high latitudes, but it couples with deep rooting in the tropics, Eastern US Grassland areas in the Western US, Central Asia, Northeastern China, and Mongolia Plateau lack strategies for water stress